Condom use in deaf young people from Mexico City: what they know and how they use it - Silvia Susana Robles-Montijo; Yuma Yoaly Pérez-Bautista (Interacciones)
Background: In studies carried out with young people without hearing impairment, the problem of considering the report of condom use as a preventive behavior is evidenced, since this by itself is not an indicator of its correct use. Objective: To evaluate the level of knowledge that deaf young people have about how to use a condom, the frequency with which they use it and the mistakes they make when using it, as well as exploring the relationship between these variables and the differences depending on the sex of the participants. Method: The Computerized Questionnaire on Sexual Health for Young Mexicans with Hearing Disabilities was used to evaluate, in a sample of 57 young Mexican deaf people (32 men and 25 women with an average age of 20.02 years), their sexual behavior, the level of knowledge on the correct use of condoms and the frequency of mistakes they make when using it during sex. Results: The main findings show that young people start their sexual life at an early age (17 years on average), have sex without using a condom, do not have adequate knowledge about how to use a condom, and those who reported using it made mistakes that were associated with breakage and slippage. Only in men was the level of knowledge negatively correlated with lifetime condom use (r=-.530, p=.002), and this, in turn, was positively correlated with frequency of failures (r=.466, p=.008). Conclusion: The study shows that young deaf people are unaware of how to use a condom and make mistakes when using it during sex, which places them in a vulnerable situation to STIs and unwanted pregnancies. The study provides evidence that highlights the need to direct efforts towards the design of training programs in the correct use of condoms for this population.